Hemingway’s Life and Works - Kawan Mohammed, Rafed (International Journal of Psychosocial Rehabilitation, 2020)
Ernest Miller Hemingway (July 21, 1899–July 2, 1961). The famous American novelist, press correspondent, short story writer, nature-adherent adventurer lover, World War I and World War II soldier, and member of the American veterans community of World War I. He is unique and distinctive with his economized and understated writing style. Simplicity is a dominant appearance in his life and literary writings. Hemingway was awarded the Pulitzer Prize in 1935 and the Nobel Prize in Literature for The Old Man and the Sea, a subtle and vivid nature image and depicting artist.